Media Komunikasi dalam Perspektif Al-Qur'an: Relevansi Tradisi Lisan dan Teknologi Digital dalam Dakwah Islam - Khiyaroh, Intiha’ul (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
In the era of globalization and advancements in information technology, Islamic communication faces the challenge of remaining relevant and effective in spreading its teachings. This study aims to analyze media communication from the perspective of the Qur'an, focusing on the roles of oral tradition and digital technology in Islamic da'wah (preaching). Additionally, this research explores the concept of media communication found in the Qur'an and its relevance to the current technological developments. The methodology used in this study is a literature review that connects Qur'anic texts with modern communication phenomena, along with an analysis of the ethical principles of Islamic communication in the context of technology. The results show that while digital technology expands the reach of da'wah, it requires the application of the ethical communication principles taught in the Qur'an, such as truth, courtesy, and caution in spreading information. This study concludes that traditional and digital media communication can complement each other in spreading Islamic values, as long as they adhere to the communication principles outlined in the Qur'an. The contribution of this study is to provide a theoretical foundation for utilizing technology in Islamic da'wah that aligns with Islamic ethical values.